Effect of temperature control on tribological and corrosion properties of copper in cathodic cage plasma nitriding - Muhammad Bilal Khalid; Syed Salman Hussain; Ameeq Farooq; Muhammad Shafiq; Yasin Khan; Muhammad Shoaib (AIP Advances)
Cathodic cage plasma nitriding (CCPN) is a proficient and cost-effective technique for surface modification of metallic samples that has been in use for the last two decades. The effectiveness of CCPN depends upon different controlled parameters. The main objective of the current study was to investigate the effect of temperature on CCPN performance. Copper (Cu) samples were nitrided at various temperatures (100–400 °C) for a fixed time of 4 h. The treated samples were investigated using a micro-hardness tester, x-ray diffraction, scanning electron microscopy, energy-dispersive x-ray spectroscopy, ball-on-disc wear tester, and potentiodynamic polarization. An improvement in hardness, wear resistance, and corrosion resistance has been reported with an increase in temperature. The treated samples possessed aluminum nitride (AlN), copper(I) nitride (Cu3N), copper(I) azide (CuN3), copper(II) azide (CuN6), and AlCu4 phases with intensity increasing with temperature. The current study clarified the reactivity of the CCPN system on treated samples in a broad manner. Untreated samples have shown abrasive wear at low temperatures, whereas adhesive wear is the predominant mechanism at high temperatures. At high temperatures, a low friction coefficient has been achieved due to smoother surfaces. Nitrided samples have shown an overall increased corrosion resistance with an increase in temperature.